Printing a patient-specific instrument guide for skull osteoma management. Issue 10 (1st October 2020) - Wang, Tien-Hsiang; Ma, Hsu; Huang, Li-Ying; Hung, Yu-Cheng; Wang, Te-Han; Yu, Wen-Chan; Chiu, Fang-Yau; Wang, Shyh-Jen; Chen, Wei-Ming
Abstract : Background: To surgically remove osteoma and to keep an optimal cosmetic profile would be very challenging. To solve the difficulty, we utilized the three-dimensional (3D) printing technologies in generating a patient-specific instrument guide (PSIG) for the safe removal of a skull bone tumor. Methods: The preoperational brain computed tomography (CT) provided the digital imaging with thin slices, and then images were reconstructed into a 3D skull model. Based on the model, we designed a PSIG to make landmarks on the osteoma to avoid excessive removal of the skull bone. During the operation, the surgeons could remove the osteoma piece by piece by using the landmark as a reference point. Results: The PSIG was successfully applied to remove an osteoma that measured 60 × 48 × 40 mm 3 over the left frontoparietal skull of a female patient. The 3D CT reconstruction taken both before and 4 months after surgery showed a significant change in the appearance of the osteoma. Conclusion: The PSIG was able to guide the surgeon in the safe removal of the skull osteoma, as well as in maintaining the cosmetic skull profile.